Práticas de leitura em Cajazeiras PB (1930 a 1950): memórias de ex-professoras - Albuquerque, Simone Formiga (2010)
The following dissertation aims to characterize the practices of reading in Cajazeiras in the period from 1930 a 1950. To be able to achieve the proposed aim, the reserach is supported on the theoretical-methodological perspective of New Cultural History and adopts as essential methodology the oral history. Therefore, through interviews with three retired teachers, this work tried to reveal their memories on the subject reading. From the interpretation of teacher s narratives emerged relevant informations about the teacher s reading ways, reading materials they read and the meaning of reading to the teachers. Finally, this investigation inserted in the field of memory and the documentary research and literature constitutes an attempt to contribute to the writing of reading history in Cajazeiras.